MENINGKATKAN KEMAMPUAN ANAK DALAM BERHITUNG MELALUI METODE BERNYANYI DENGAN MEDIA FLASH CARDS (Studi Deskriptif di RA Al-Furqon Kabupaten Ciamis) - Revita Yanuarsari; Ella Dewi Latifah; Lisnawati (Pusat Riset dan Inovasi Nasional, 2022)
This research is motivated by the lack of numeracy skills of 1-10 students at RA Al-Furqon. This study aims to determine how the planning, implementation and results of using the singing method using flash cards media to improve children's numeracy skills. This study uses a qualitative descriptive research method. Sources of data used through questionnaires, interviews, observations, documentation and literature studies. From the results of this study, it was concluded that the singing method through flash cards was proven to improve numeracy skills in group A children in RA Al Furqon, Ciamis Regency.